2017
DOI: 10.1007/s11605-017-3520-0
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Outcomes of Single-Incision Versus Conventional Laparoscopic Surgery for Colorectal Diseases: Meta-Analysis of Randomized and Prospective Evidence

Abstract: The results based on randomized and prospective evidence provide convincing support for the clinical similarity that SILS is basically as applicable, effective, and safe as CLS when dealing with colorectal lesions, but not for superiority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Several published meta-analyses evaluating SLIS versus CLS have shown that short-term clinical and oncological outcomes of SILS are better than that of CLS [ 4 ]. Li et al had very fully confirmed that SILS had less blood loss, shorter incision length, shorter and hospital stay but longer operative time for colorectal disease [ 5 ]. However, laparoscopic sigmoid and rectal surgery based on these two techniques has rarely been studied by meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Several published meta-analyses evaluating SLIS versus CLS have shown that short-term clinical and oncological outcomes of SILS are better than that of CLS [ 4 ]. Li et al had very fully confirmed that SILS had less blood loss, shorter incision length, shorter and hospital stay but longer operative time for colorectal disease [ 5 ]. However, laparoscopic sigmoid and rectal surgery based on these two techniques has rarely been studied by meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Some meta-analyses also revealed that SILS-colectomy was associated with shorter hospital stay compared to conventional laparoscopic colectomy. [1112] In addition, the learning curve revealed a dramatic shortening in operating time as experiences with RPLWP grew; the mean operating time for the last five cases was almost similar to CLWP. These results suggest that RPLWP is an effective, safe, minimally invasive procedural alternative to CLWP with no disadvantage for patients when the well-trained surgeon performs it.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic gastrectomy (LG) has such potential benefits as reducing post-operative complications and accelerating healing. [15] Group ASA: American Society of Anesthesiologists.…”
Section: Discussionmentioning
confidence: 99%